Determinants of Employee Engagement in Universiti Sains Malaysia - Kok Ban Teoh; Chun Qi Teoh; Wei Hao Tew; Thaqif Farhan Ziad; Xin Nee Thoo; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
For higher education corporations that are constantly striving to improve service quality, employee retention and organizational performance, employee commitment is the most important key. This study was conducted to examine the factors that will affect employee commitment at Universiti Sains Malaysia. The specific objectives are as follows: (1) to examine the effects of support provided by the organization and perceived by employees, leadership styles, appreciation and recognition on employee commitment; (2) to examine the effects of job flexibility, career opportunities and work-life balance on employee commitment; (3) to examine the role of internal communication as a mediator in these key factors and overall employee commitment. Our findings show that career growth, interpersonal relationships, role clarity, and work environment have significant positive effects on employee engagement among 150 USM staff, with role clarity emerging as the strongest predictor. Employee involvement was not found to have a significant independent effect. These findings indicate that employees are more engaged when they experience clear job expectations, supportive relationships, opportunities for professional development, and a conducive work environment, offering practical guidance for university management to strengthen employee engagement.